Peningkatan Pengetahuan Tentang Keamanan Bandar Udara Pada Penyelengaraan Jamaah Ibadah Umroh Melalui Penyuluhan Online - Laila Rochmawati; Dewi Ratna Sari; Didi Hariyanto; Fatmawati; Lady Silk Moonlight (Jurnal Pengabdian Kepada Masyarakat (JPKM) Langit Biru, 2021)
The target of this counseling is Umrah pilgrims and high school aviation teachers who do not understand airport security. The identification of problems with the understanding of pilgrims' umrah pilgrimage for smk aviation teachers on airport security is still relatively low; knowledge of dangerous goods for pilgrims is low; travel that has not provided information about airport safety. The solution to the problem is by increasing the understanding of the Umrah pilgrims about airport security by providing information about airport safety; increase knowledge of dangerous goods for pilgrims to worship Umrah; provide travel education about airport safety. Alternative solutions to problems taken by airport security counseling for Umrah pilgrims. The stages and methods of implementing the target participant survey program; preparation of infrastructure advice; Airport Extension methods; program evaluation; reporting.